2004
DOI: 10.1111/j.1463-1318.2004.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after placement of colorectal stents

Abstract: Background Colonic stents are increasingly used to palliate or alleviate large bowel obstruction in patients with colon cancer and other obstructing lesions in whom a definitive surgical procedure is inappropriate. We report on the outcomes of a large group of patients who underwent deployment of a colon stent in a single institution by a single operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…All stents were inserted under radiological guidance using an 'over the wire ' Data were collected by review of patient case notes and investigation reports using a pro forma, and analysed using SPSS  version 15 (SPSS, Chicago, Illinois, USA). This study followed on from a previous series reporting on patients undergoing colonic stent insertion at this institution between September 1995 and May 2002 11 , but there was no overlap with the data reported here. In this study 'palliation' referred to use of SEMS to provide symptomatic relief in patients with co-morbidities rendering them unfit for surgical intervention, and 'elective' indicated a planned procedure, undertaken on the next available list.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…All stents were inserted under radiological guidance using an 'over the wire ' Data were collected by review of patient case notes and investigation reports using a pro forma, and analysed using SPSS  version 15 (SPSS, Chicago, Illinois, USA). This study followed on from a previous series reporting on patients undergoing colonic stent insertion at this institution between September 1995 and May 2002 11 , but there was no overlap with the data reported here. In this study 'palliation' referred to use of SEMS to provide symptomatic relief in patients with co-morbidities rendering them unfit for surgical intervention, and 'elective' indicated a planned procedure, undertaken on the next available list.…”
Section: Methodssupporting
confidence: 56%
“…The remaining patient died 1 day after stent insertion owing to sepsis from presumed bowel perforation, although no imaging was undertaken to confirm this and it is not known whether the perforation was secondary to stent insertion or ongoing obstruction. Similarly poor outcomes in this group were encountered in the previous series from this institution 11 .…”
Section: Complicationsmentioning
confidence: 62%
“…1 Many systematic reviews found that stents can alleviate intestinal obstruction and stenosis in patients. 2 Metal self-expanding stent has been used for treatment of the stenosis and obstruction of bowel and vessels for three decades.…”
Section: Introductionmentioning
confidence: 99%
“…Überlebenszeiten angegeben (z.B. 42 Tage [5] oder 88 Tage [6]) und Komplikationsraten von kumulativ 30–70% als «acceptable» betrachtet werden.…”
Section: Literaturanalyse 1990–2012 Mit Schwerpunkt 2011/2012unclassified